Echoes of Krafft-Ebing’s Psychopathia Sexualis in Scientific Periodicals: Sexual and Mental Pathology in Late Nineteenth- and Early Twentieth Century Medical Discourse - Annalisa Federici (Lea)
This essay proposes a corpus-based terminological analysis of the language of moral decadence, sexual deviance and mental degeneration introduced and/or popularised by Richard von Krafft-Ebing’s Psychopathia Sexualis. It also investigates the resonance that this domain-specific terminology may have had in British medical journals between the late nineteenth and early twentieth century, when periodicals played a crucial role in propagating various forms of medical discourse. Corpus linguistics methodology is employed to scrutinise Krafft-Ebing’s treatise, particularly to extract and contextually analyse specialised terms in the domain of sexual and mental pathology which might have contributed to the dissemination of psychiatric and sexological discourses of decadence and degeneration. Once a set of terms has been individuated, their frequency and collocational behaviour is examined in a corpus of scientific articles from a leading nineteenth-century specialist periodical, the Journal of Mental Science. Since terms represent concepts within a specific domain, this essay aims to bridge linguistic and historical investigation of medical discourse by demonstrating that a corpus-based terminological analysis can provide useful insights into the specialised knowledge, cultural values and ideological positionings of a particular community of experts, and the various domain-specific discourses it contributed to circulate.